Parental knowledge and attitudes regarding asthma in their children: Impact of an educational intervention in an Indian population. Issue 3 (21st January 2020) - Divecha, Chhaya A.; Tullu, Milind S.; Jadhav, Devika U.
Abstract: Introduction and Objectives: Research shows positive effects of asthma education in improving parental knowledge, self‐management skills, and reducing healthcare costs. Such studies are lacking in resource‐limited countries. We studied the effectiveness of educational intervention in improving the knowledge and attitudes of parents/caregivers of asthmatic children. Methods: The study was conducted in the pediatric chest clinic of tertiary hospital (India) over 21 months after ethics committee approval. Recruited parents were randomized into the interventional group (A) receiving education module and control group (B). Parents' asthma knowledge and attitudes were assessed at baseline and 5 months postenrollment using 25‐item questionnaire. Detailed demographic data, clinical data, and exacerbations during study were noted. Results: A total of 75 parents/guardians fulfilling inclusion criteria were analyzed (cases/group A: 37 and controls/group B: 38). 8.3 percent of parents/caregivers were illiterate. Around 36.9% of patients had a family history of allergy/asthma. Mean knowledge scores at follow‐up were 12.24 and 9.89 for groups A and B, respectively ( P  < .05). Parents did better on knowledge items related to chronicity, family history, chronic cough, home administration of steroids in acute severe asthma, and maintaining records of clinical/medications for good control. Intervention group (A) showed significant improvement in most attitude‐based questions postintervention as compared with the nonintervention group (B). There was no statistically significant difference in asthma severity and control between the two groups at follow‐up. Conclusions: Small group education on asthma in parents/caregivers improves their knowledge and attitudes. Healthcare plans should invest in pediatric asthma education and identify key personnel/opportunities to impart the same in routine care.